A path planning method for a surface inspection system based on two-dimensional laser profile scanner. (16th July 2019) - Li, Lina; Xu, De; Niu, Linkai; Lan, Yuan; Xiong, Xiaoyan
In this article, a method for two-dimensional scanning path planning based on robot is proposed. In this method, a section division algorithm based on neighborhood search method for scanning orientation determination is firstly produced. The scanning paths which meet constraints of the system are then generated. Finally, the experiment is carried out on robot-based scanning platform. The two-dimensional data from scanner and the robot position are combined to form three-dimensional surface data of measured workpiece. The experiment results verify the effectiveness of proposed method.